Vanadium-containing ordered mesoporous silicas: synthesis, characterization and catalytic activity in the hydroxylation of biphenyl - George, J.; Shylesh, S; Singh, AP (Applied Catalysis A - General, 2005)
A series of vanadium-containing ordered mesoporous MCM-41 materials (V-OMS) have been synthesized by direct hydrothermal (VMCM-41) and grafting (V/MCM-41) methods using hexadecyl trimethyl ammonium bromide (HDTMABr) as the structure-directing agent. The physico-chemical properties of the vanadium-containing materials were characterized in detail by ICP-OES, XRD, Fr-IR, N-2 adsorption-desorption, DRUV-VIS, TPR, XPS and SEM techniques. The redox performances of the vanadium-modified mesoporous materials were tested in the hydroxylation of biphenyl using aqueous H2O2 (30 wt.%) as oxidant. For a better exploitation of the catalytic activity, the reaction parameters are optimized in terms of temperature, solvent, oxidant, etc. A comparison between the catalytic activity values of the vanadium-containing mesoporous materials prepared by the two routes shows that vanadium-substituted (V-MCM-41) materials had increased activity and improved selectivity for mono hydroxyl products in the hydroxylation reaction of biphenyl compared to the V/MCM-41 catalysts. The heterogenity of the catalysts was verified by a series of leaching studies. Both the catalysts enhance the leaching of active vanadia species during the reaction; among them, V/MCM-41 shows the least heterogenity. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: biphenyl; heterogenity; MCM-41; Mesoporous molecular sieves; Vanadium

Vanadium-containing ordered mesoporous silicates: does the silica source really affect the catalytic activity, structural stability, and nature of vanadium sites in V-MCM-41? - Shylesh, S; Singh, AP (Journal of Catalysis, 2005)
A series of vanadium-substituted mesoporous materials were synthesized hydrothermally with the use of two commonly used silica Sources. fumed silica and tetra ethyl orthosilicate. The extent of mesopore structural ordering was confirmed from X-ray diffraction, N-2 physisorption, SEM, and TEM, and the presence and nature of vanadium species inside the framework of the MCM-41 matrix was confirmed in detail with the use of various characterization techniques like FT-IR, Si-29 MAS NMR, DRUV-vis, EPR, V-51 MAS NMR, and Raman analysis. It is deduced from the above characterization techniques that, regardless of the silica source, vanadium is incorporated into the silica framework and thereby increases the structural ordering and wall thickness of the mesoporous material. Thermal and hydrothermal Studies performed over the V-MCM-41 catalysts show that the Si-O-Si inorganic backbone from a fumed silica source is more resistant to severe thermal treatments and hydrolysis than the tetraethyl orthosilicate-synthesized catalysts. Spectroscopic characterization reveals the existence of easily accessible isolated tetrahedral vanadium sites on V-MCM-41 catalyst prepared front fumed silica catalyst, whereas the sample obtained from a tetraethyl orthosilicate silica Source shows vanadium in more disordered sites. Catalytic results show that both catalysts display excellent activity toward the epoxidation reaction of bulkier olefins, and the exceptional activity of the fumed silica catalyst may arise from the more isolated tetrahedral sites and the complementary textural characteristics, which may facilitate the easy access of substrate to the isolated framework metal sites. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: epoxidation; fumed silica; MCM-41; tetraethyl orthosilicate; Vanadium